Active tracking of rotational mode heliostat - Tan, Boon Kok (2004)
Active traclung methods for rotational mode heliostat invented by Prof. Dr. Y. T. Chen recently, are proposed in this thesis. This is to provide an alternative tracking method for Non-Imaging Focusing Heliostat (NIFH) designed by UTM that is simple and cost effective, with reasonable performance. The newly developed methods consist of two parts: primary tracking and secondary tracking. For primary tracking, a sensor plane, which is built up of a gnomon surrounded by eight photo-detectors, is used to detect the deviation of incident angle of incoming sunray. In principle, the normal of the sensor plane should always point towards the direction of the sun. The displacement of the incoming sunray will be sensed by comparing the intensity difference of the photodetectors, as the gnomon will cast a shadow onto a portion area of photo-detectors' surface. The proposed tracking method is autonomous and stand-alone. The entire sensing and motor-controlling task is performing by using a simple electronic circuit, attached on the body of the heliostat. No complicated computer software control is needed. In addition, open-loop clock-like signal will be fed into the system to fbther increase the speed of error compensation and for better stability performance. For 8 secondary tracking, the use of mechanical cam drive by consistent clock is proposed. From the study of NFH's tracking equation, a high-precision mechanical cam is proposed to compensate the aberration of slave mirror throughout the tracking day. The merits of these methods are the larger range of dynamic range for the sensors and their simple designs.